STRUCTURAL AND SEMANTIC FEATURES OF POLYCOMPONENT COMPOSITE SENTENCES IN ENGLISH (International journal of artificial intelligence, 2026)
This article provides a systematic analysis of the structural-semantic types of polycomponential composite sentences (PCCS) in the English language. The study examines the theoretical foundations of PCCS, the syntactic relations between components (coordinative, subordinate, and mixed), as well as their communicative and pragmatic functions. Based on examples drawn from literary texts, the structure and semantic features of various PCCS models are identified and described. The findings of the research demonstrate that polycomponential composite sentences function as complex, multi-level units within the syntactic system, contributing to the dynamic and expressive development of discourse.